(untitled) (Journal of Economic Research & Business Administration, 2016)
Insurance companies relates to the field of services and its aim is to provide insurance coverage, which includes the right of the insured to receive cash compensation in case of agreed in advance consequences of insurance claims, as well as the obligation of the insurer to pay the corresponding insurance compensation. The guarantor of stability to any organization is a high level of organization control system, one of basic elements of which is the properly organized internal audit. The attracted structures for realization of internal audit mostly are large consulting or public accountant organizations. Process of creation of independent audit, providing realization of practical public necessity are validifying of finan-cial information in interests of the users of this information - proceeds in our republic already a few years.